2019
DOI: 10.1242/jcs.221390
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of genes encoding the nuclear envelope LINC complex in the monocot speciesZea mays

Abstract: The LINC (Linker of Nucleoskeleton to Cytoskeleton) complex is an essential multi-protein structure spanning the nuclear envelope. It connects the cytoplasm to the nucleoplasm, functions to maintain nuclear shape and architecture, and regulates chromosome dynamics during cell division. Knowledge of LINC complex composition and function in the plant kingdom is primarily limited to Arabidopsis, but critically missing from the evolutionarily distant monocots which include grasses, the most important agronomic cro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 93 publications
0
20
0
Order By: Relevance
“…Their N termini are located in the nucleoplasm and associate with lamin-like proteins, whereas their C termini contain the SUN domain and associate with outer nuclear membrane Klarsicht/ANC-1/Syne-1 Homology (KASH)-domain proteins that interact with the cytoskeleton. SUN and KASH domain proteins form the LINC complex, which connects the nucleoskeleton to the cytoskeleton (Meier et al, 2017;Gumber et al, 2019). Previous studies have suggested that LINC complexes are involved in regulating nuclear movement, nuclear positioning, nuclear morphology, and chromatin-nuclear envelope interactions (Starr and Fridolfsson, 2010;Tapley and Starr, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Their N termini are located in the nucleoplasm and associate with lamin-like proteins, whereas their C termini contain the SUN domain and associate with outer nuclear membrane Klarsicht/ANC-1/Syne-1 Homology (KASH)-domain proteins that interact with the cytoskeleton. SUN and KASH domain proteins form the LINC complex, which connects the nucleoskeleton to the cytoskeleton (Meier et al, 2017;Gumber et al, 2019). Previous studies have suggested that LINC complexes are involved in regulating nuclear movement, nuclear positioning, nuclear morphology, and chromatin-nuclear envelope interactions (Starr and Fridolfsson, 2010;Tapley and Starr, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, tryptophan-proline-proline (WPP)-domain interacting proteins ( Xu et al, 2007 ), WPP-interacting tail-anchored (WIT) proteins ( Zhou et al, 2012b ) and SUN-domain-interacting nuclear envelope (SINE) proteins ( Zhou et al, 2014 ) were identified as plant-specific outer nuclear membrane proteins. Recently, a new grass-specific KASH protein family has also been reported in Z. mays ( Gumber et al, 2019 ), including the Z. mays LINC complex proteins KASH grass-specific 1 ( Zm MLKG1) and Z. mays LINC KASH At WIP-like 1 and 2 ( Zm MLKP1 and Zm MLKP2) proteins, which were shown to interact with the inner nuclear membrane protein Zm SUN2 at the nuclear periphery.…”
Section: Nuclear Envelope Bridge Complexes – a Mechanism Ensuring Chrmentioning
confidence: 99%
“…Plant KASH proteins were first identified in Arabidopsis, through identification of a transmembrane domain, a shorter luminal tail domain (9-15 aa), and a similar characteristic C-terminal tail, terminating in a consensus 'XVPT' motif [3,4]. Homologs of Arabidopsis SUN and KASH proteins have subsequently been found in a variety of land plant species [5] and functionally investigated in Z. mays and M. truncatula [4,6,7,8]. The first identified plant KASH proteins, WPP-Interacting Proteins (WIPs) 1, 2 and 3, along with their ONM interaction partners the WPP-Interacting Tail Anchored Proteins 1 and 2 (WITs), form a LINC complex with Arabidopsis SUN1 and SUN2 [3].…”
Section: Introductionmentioning
confidence: 99%